Amine functionalized radiation induced grafted polyolefin nanofibers for CO2 adsorption. (March 2019) - Abbasi, Ali; Nasef, Mohamed Mahmoud; Kheawhom, Soorathep; Faridi-Majidi, Reza; Takeshi, Matsuura; Abouzari-Lotf, Ebrahim; Choong, Thomas
Abstract: A new type of nanofibrous amine-containing adsorbent was prepared for CO2 adsorption by electrospinning of syndiotactic polypropylene (s-PP) followed by radiation induced grafting of glycidyl methacrylate and subsequent amination with ethanolamine. The obtained adsorbents were tested for CO2 adsorption with a mixture of CO2 /N2 having 5–15% CO2 using a fixed bed adsorption column at atmospheric pressure. A maximum adsorption capacity of 2.87 mmol/g was achieved for the sample with degree of grafting of 300% and degree of amination of 94% at feed concentration of 15% at 30 °C. This was accompanied by good mechanical characteristics and a very high amine efficiency that reached 75% at room temperature, suggesting that the obtained fibrous adsorbent has high potential for CO2 adsorption. Graphical abstract: fx1 Highlights: CO2 adsorbent was prepared using electrospinning, grafting and amination. Polypropylene fibers with diameter of 439 nm and surface area of 2 m 2 /g prepared. Grafting of glycidyl methacrylate was completed with grafting degree of 445%. Grafted nanofibers were aminated with ethanol amine with degree of amination of 98%. The adsorbent showed high amine efficiency of 75% and good regeneration stability.